Supply Response of Sudan's Cotton Industry: Implications of Government Intervention - Elawad Salih, Salah Mohamed (2001)
Sudan's cotton industry has assumed a key role since the mid 1920's in its national economic development both on economic and social grounds. This study addresses the issues of government intervention on Sudan's cotton industry. Control measures in the cotton industry which span area determination, cotton producers' price determination, cotton exchange rate and cotton tax rate, are believed to have negative impacts on the cotton industry supply response. The major objective of this study is to investigate the implications of government intervention on cotton industry. The study employs an econometric approach to examine the behavior of the cotton supply response. The study uses time series data over the period 1969 - 1998. The long and medium staple cotton models incorporate five equations, namely area, yield, export supply, producers' price and export demand The model equations have been structured to allow for a balanced representation of both price and nonprice factors. The models have been estimated using the auto--regressive distributed lag technique and error correction model The study employs Theil's inequality and root mean square percentage error as validation techniques to ascertain model performance. A simulation of alternative policy scenarios with regard to cotton exchange rate and cotton tax rate was carried out to assess the impact of policy reforms on the magnitude of the endogenous variables. In addition, a simulation of the policy scenario with regard to food self-sufficiency as a policy objective was also conducted. The findings of the study support the view that government interventions on Sudan's cotton industry have had negative implications on the cotton supply function components, namely, area and yield The various forms of government intervention have had, on the whole, undermined the provision of adequate incentives to cotton producers and as such have resulted in the lack of responsiveness on part of the cotton producers to changes in the cotton world market. Such a situation has deprived the country of its inherent comparative advantage as cotton producer. The study recommends corrective policy reforms in relation to producers' price determination mechanism and its associate variables mainly cotton exchange rate and cotton taxation. Moreover, non-price policy variables, which are mainly of technological nature, have to be appropriately considered in cotton production planning process in order to elucidate positive supply response.